Penggunaan Media Konkret Berbasis Project Based Laerning (PJBL) dalam Upaya Peningkatan Kemampuan Berbicara Anak Speech Delay di Taman Kanak-Kanak - Marthina Rona Bara; Atien Nur Chamidah (Jurnal Ners, 2025)
This study aims to determine the effectiveness of using concrete media based on Project Based Learning (PjBL) in improving the speaking skills of young children with speech delays in kindergarten. The method used is Classroom Action Research (CAR) with a qualitative approach, conducted in two cycles. The research subjects consisted of two children out of a total of 12 children in the class. Data was collected through observation sheets, documentation, and tests in the form of observations and final assessments of speaking skills. The results of the study showed that the use of concrete media based on PjBL can significantly improve children's speaking skills. This was evident from the increase in participation scores and language skills of the children from pre-action to cycle II. At the beginning, student AC scored 46% (sufficient category) and ZA scored 33% (sufficient category). After cycle I, AC improved to 57% (good category) although it did not reach the KKTP 70% threshold, while ZA scored 43% (sufficient category). In Cycle II, AC reached 79% (very good category) and ZA 75% (good category). The implementation of concrete media based on PjBL can be used as an effective alternative learning strategy to develop children's speaking skills, especially for those with speech delays.